2012
DOI: 10.1212/wnl.0b013e3182698d7c
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion of stent graft from the carotid artery

Abstract: A stent graft was deployed to treat a postcarotid endarterectomy pseudoaneurysm in a 52-year-old man. One and a half years later, he developed asymptomatic extrusion of the stent graft. CT angiography showed stent extrusion with occlusion of the right carotid artery (figure). The stent was explanted uneventfully. Stent extrusion is very rare.1 Reasons for stent extrusion include stent undersizing, ongoing pseudoaneurysm expansion, or carotid blowout at the time of stent deployment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The patient was treated by transoral removal of the extruded stent. 4 Maramattom et al 5 described stent-graft extrusion occurring 1.5 years after stent placement for treatment of a post–carotid endarterectomy pseudoaneurysm. The patient had presented 1.5 years after stent placement with an occluded carotid artery, and the stent graft was removed uneventfully.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient was treated by transoral removal of the extruded stent. 4 Maramattom et al 5 described stent-graft extrusion occurring 1.5 years after stent placement for treatment of a post–carotid endarterectomy pseudoaneurysm. The patient had presented 1.5 years after stent placement with an occluded carotid artery, and the stent graft was removed uneventfully.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators reported stent undersizing and pseudoaneurysm expansion as predisposing factors to extrusion. 5 Warren et al 6 reported two cases of covered stent extrusion in patients treated for carotid blowout syndrome. These cases demonstrate that stent-graft extrusion is not limited to an anatomic or arterial location and that it might be associated with stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%